Estudo de um isolante térmico para tubos fabricado em material compósito - Santana, José Jorge Barros de (2011)
It presents a new type of insulation for ductwork hot water, which can be used in solar systems for heating water, which consists of a composite of different compositions based on plaster, cement and EPS ground, palm and water. This composite has as its main features easy assembly and manufacturing processes and low cost. Comparative results will be presented on the tests of materials and thermal tubes proposed. Four formulations were used to manufacture tubes with three diameters 70, 65 and 42mm. It was also tested conventionally used for elastomeric foam insulation to 110 ° C, for a comparative analysis with the composite pipe insulator proposed. It will demonstrate that the cost of manufacturing of such tubes is competitive with alternative elastomeric foam tested, but results of the composite tube to the temperature range studied, are lower. Another drawback of the composite insulator tube is its large mass. It would be important to test such a composite for greater levels of temperature to a diagnostic technique competitive with conventionally used insulators. A positive factor of using the proposed composite-tube would be the recycling of EPS so damaging to the environment, representing an environmentally friendly application of science